CA-125-indicated asymptomatic relapse confers survival benefit to ovarian cancer patients who underwent secondary cytoreduction surgery - Wang Fang; Ye Yanfen; Xu Xia; Zhou Xuehui; Wang Jinhua; Chen Xiaoxiang (BMC, 2013)
Abstract Background There is no consensus regarding the management of ovarian cancer patients, who have shown complete clinical response (CCR) to primary therapy and have rising cancer antigen CA-125 levels but have no symptoms of recurrent disease. The present study aims to determine whether follow-up CA-125 levels can be used to identify the need for imaging studies and secondary cytoreductive surgery (CRS). Methods We identified 410 ovarian cancer patients treated at The University of Texas MD Anderson Cancer Center between 1984 and 2011. These patients had shown CCR to primary therapy. Follow-up was conducted based on the surveillance protocol of the MD Anderson Cancer Center. We used the Cox proportional hazards model and log-rank test to assess the associations between the follow-up CA-125 levels and secondary CRS and survival duration. Results The CA-125 level of 1.68 × nadir was defined as the indicator of recurrent disease (p < 0.001). The specificity and sensitivity of this criterion were 82.9% and 85.6%, respectively, and the median lead-time of the CA-125 biochemical progression prior to clinically-defined relapse was 31 days (ranging from 1 to 391 days). The median number of the negative imaging studies for the clinical relapse findings in patients with a CA-125 level of < 1.68 × nadir was 3 (ranging from 0 to 24 times). The increase of CA-125 level at relapse was an independent predictor of overall and progression free survival in patients who had shown CCR to primary therapy (p = 0.04 and 0.02 respectively). The overall and progression free survival durations in patients with a CA-125 level ≤ 1.68 × nadir at relapse (69.4 and 13.8 months) were longer than those with a CA-125 level > 1.68 × nadir at relapse (55.7 and 10.4 months; p = 0.04 and 0.01, respectively). The overall and progression free survival duration of patients with asymptomatic relapse and underwent a secondary CRS was longer than that of patients with symptomatic relapse (p = 0.02 and 0.04 respectively). Conclusions The increase of serum CA-125 levels is an early warning of clinical relapse in ovarian cancer. Using CA-125 levels in guiding the treatment of patients with asymptomatic recurrent ovarian cancer, who have shown CCR to primary therapy, can facilitate optimal secondary CRS and extend the survival duration of the patients.